Determinan Keputusan Pembelian Mahasiswa pada Marketplace Lazada - Akhyar, Muhamad Khairul; Junita, Audia; Fahlevi, Alvin (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The industrial revolution 4.0 has had a major impact on the world's ecosystem and way of life. Human behavior in shopping has changed along with the development of the technological era. One of the changes is the rise of online shopping. This study analyzes the determinants of students' purchasing decisions on the Lazada marketplace, including consumer trust, promotion, and purchase interest. The study was conducted using a quantitative approach. The population of the study was 427 students of the Management Study Program, Faculty of Economics and Business, Harapan University, Medan, and a sample of 206 students selected using the proportional random sampling technique. Primary data were collected through the distribution of online google-form questionnaires. Path analysis techniques were used to answer research problems and hypotheses. The results of the study prove that consumer trust and promotion have a significant direct effect on students' purchasing decisions on the Lazada marketplace, as well as consumer trust and promotion have a significant effect on students' purchasing decisions on the Lazada marketplace through purchase interest as an intervening variable.